Calretinin immunohistochemistry for the diagnosis of Hirschprung disease in rectal biopsies - CİNEL, ZELİHA LEYLA (ELSEVIER GMBH, 2015)
In this study we aimed to evaluate the usability of calretinin staining in the diagnosis and exclusion of HD in 36 rectal biopsies. Through immunohistochemical examination, in of a total of 21 pediatric patients in whom ganglion cells were detected in first rectal biopsies and in re-biopsies, ganglion cells were seen through nuclear and cytoplasmic staining. In the lamina propria and superficial submucosa, staining of nerve fibers was detected in a granular pattern in varying intensities. Out of a total of 5 biopsies (including one re-biopsy) of non-HD patients, where ganglion cells could not be seen, the nerve fibers were all stained. On the other hand, in 10 HD patients, diagnosed by a colon pull through operation, calretinin staining was not detected in any area of the rectal biopsies except for the mast cells. We conclude that calretinin immunostaining for the diagnosis of HD is an easy and reliable method for use in daily practice. (C) 2014 Published by Elsevier GmbH.
Keywords: Hirschprung disease; Calretinin; Immunohistochemistry; Ganglion cell; HIRSCHSPRUNGS-DISEASE; ACETYLCHOLINESTERASE HISTOCHEMISTRY; SUCTION BIOPSIES; NEURONS; EXPRESSION; PATHOLOGY; PROTEIN